Mathematical Argumentation Ability: Error Analysis in Solving Mathematical Arguments - INDRAWATİNİNGSİH, Nonik; -, Purwanto; AS'ARİ, Abdur; SA'DİJAH, Cholis (Journal for the education of gifted young scientists, 2020)
This study aims to analyze errors made by students in solving mathematical arguments based on Bloom’s Taxonomy. It is a quantitative descriptive study. As many as 72 students of a senior secondary school were involved as the participants. The Mathematical Argumentation Ability Test (TKAM) was developed based on the cognitive domain of Bloom’s Taxonomy (C1 to C6), and later distributed to the participants. The scores obtained from the test were analyzed. The results show that only 31% of students pass the test while 69% of students fail. Many students do not pass the test due to procedural errors and conceptual errors in solving the problems. Furthermore, based on Bloom’s Taxonomy, students who able to solve the problems only achieve the C3 level of cognitive domain, namely the ability to draw conclusion arguments